How Employee Creativity and Motivation Shape Organizational Innovation? A Quantitative Study in Human Resource Management - Rifki Suwaji; Anastasia Anut; Maria Melania Jaisa; Philipus Hadit; Eric Annasyah (Journal of Economic Education and Entrepreneurship Studies, 2025)
Organizational innovation has become a critical determinant of competitiveness in modern manufacturing firms, particularly in the era of digital transformation and dynamic market pressure. This study examines the influence of employee creativity and motivation on organizational innovation within the broader framework of human resource management. Using a quantitative associative approach, data were collected from 85 employees selected through proportionate stratified random sampling from a workforce of 500 employees in a large-scale manufacturing company. Survey responses were measured using a Likert-scale instrument, and multiple linear regression analysis was performed using SPSS version 26. The empirical results show that employee creativity significantly predicts organizational innovation (β = 0.465, p < 0.001), indicating that creative employees tend to generate novel ideas and contribute to innovation-driven practices. Motivation also demonstrates a significant positive effect (β = 0.389, p < 0.001), suggesting that motivated employees are more engaged in innovative behavior and improvement initiatives. Together, creativity and motivation account for 68.2% of the variance in organizational innovation (R² = 0.682), confirming their synergistic role as key drivers of innovation capability. The study highlights important implications for human resource management, emphasizing the need for strategic policies that nurture creativity, strengthen intrinsic motivation, and reward innovative contributions to sustain organizational competitiveness.